KEBUTUHAN PELATIHAN KADER PROGRAM PENINGKATAN PENDAPATAN KELUARGA DI ERA E COMMERCE - Elais Retnowati; Anan Sutisna; Jaenal Mutakim (Universitas Sriwijaya, 2021)
Family Income Improvement Efforts of family welfare (UP2K-PKK) program aims to reduce woman poverty by developing family business activities through MSMEs. UP2K-PKK cadres feel they do not have the knowledge and skills to increase community entrepreneurship. This research aims to find the knowledge and skills of fostering community entrepreneurship as the basis for planning the training program to improve knowledge and skills for UP2K-PKK Cadres. The method used in this study is mixed methods research. Determination of training needs had done with Training Needs Analysis. The study respondents were all UP2K-PKK Cadres companion MSMEs in Cipayung East Jakarta.The results concluded that UP2K-PKK Cadres need knowledge related to soft skills, namely techniques to motivate people to join the UP2K program, knowledge related to hard skills, namely; 1) managing finances, 2) Marketing techniques, and 3) techniques for identifying the learning needs of UP2K partners. Amid busyness as a housewife, UP2K-PKK Cadres has the willingness to improve their capacity building. Cadres should have the ability to direct the MSMEs to adapt and increasingly modern marketing ways so as not to be left behind and lose the opportunity to get the market.